Self- Acceptance of Adolescents Who Have Stepfamilies in Talang Kelapa (Phenomenological Approach) - Oktaviani, Silfania; Itryah, Itryah (Granada El-Fath, 2024)
This study aims to determine the self-acceptance of adolescents who have stepfamilies. Which of the self-acceptance factors affect the self-acceptance of adolescents who have stepfamilies. This study uses a qualitative research design and uses phenomenological studies to be able to find out the self-acceptance of adolescents who have stepfamilies. In this study, researchers used 7 sources, 2 people as research subjects, 5 people as informants know. The results of this study found that there were causes for the two subjects to accept themselves to their stepfamilies. Both subjects have 2 self-acceptance factors. Each factor that both subjects have is also influenced by self-concept and social environment.